ELECTRONIC RESOURCES IN EDUCATION: ADVANTAGES OF THE DIGITAL APPROACH OVER TRADITIONAL TEACHING METHODS (Uzbekistan Open Conference, 2025)
The article examines the main advantages of electronic educational resources (EER) compared to traditional printed textbooks. It analyzes such aspects as interactivity, multimedia features, mobility, and the possibility of continuous information updates. Electronic resources provide a higher level of student engagement, personalized learning, and interactive interaction with educational content. Special attention is paid to the role of EER in the modern digital educational environment and their impact on the quality of the learning process.